Penjaminan Kualitas Sistem Informasi Point Of Sale Berbasis Web Menggunakan Standar ISO/IEC 29119 - Jodi Caesar; Wasis Wijanarko; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
Software Quality Assurance (SQA) plays a pivotal role in maintaining the operational stability and data integrity of business-critical applications, particularly Point of Sale (POS) Information Systems where transaction accuracy is paramount. This study aims to rigorously evaluate the functional quality and security posture of an open-source, web-based POS application acquired from a public GitHub repository. The testing methodology was systematically executed using a Black-Box Testing approach, strictly adhering to the ISO/IEC 29119 process framework to ensure a standardized testing lifecycle. The quality evaluation was grounded in the ISO/IEC 25010 standard, with a specific focus on the Functionality and Reliability characteristics. The testing process involved the design and execution of 25 comprehensive Test Cases covering various user scenarios, resulting in the documentation of 6 distinct Bug Reports. Although the fundamental workflows function as intended, the assessment revealed significant defects, comprising 1 Critical Bug and 5 Major Bugs. The most severe Critical Bug involves the system's failure to automatically deduct inventory stock following a successful transaction, a flaw that directly compromises data integrity and inventory accuracy. Additionally, critical security vulnerabilities, specifically SQL Injection, were detected within the authentication module, posing severe risks of unauthorized access. Consequently, the POS application is classified as